"I played a song with the help of a magic banana": assessing short-term making events. Issue 3 (28th June 2021) - Nixon, Jessie; Halverson, Erica; Stoiber, Andy; Garbacz, Andy
Abstract : Purpose: The purpose of this study is to understand how learners describe their experiences with short-term, introductory maker experiences and to test a method for assessing learners' experiences authentic to short-term learning. Design/methodology/approach: The authors collected written responses from participants at a two-day event, STEM Center Learning Days. Through an analysis of 707 unique instances of learner responses to participation in drop-in maker activities, they examined how participants describe their short-term learning experiences. Findings: The authors found that although some activities appear to onlookers to create passive experiences for learners, these seemingly passive moments have a significant impact on learners. In addition, some learners described themselves as working in tandem with tools to make something work and other learners viewed the tools as working autonomously. They found that the assessment method allowed them to gain an understanding of how learners describe their experiences offering important implications for understanding short-term learning events. Originality/value: The findings provide researchers studying short-term learning in its natural setting a new method to understand how learners make sense of their individual experience. Further, designers of short-term learning experiences may gain insights into their unique activities and indications of where additional guidance and scaffolds will improve small learning moments.